(untitled) (Forum Agribisnis, 2023)
Bogor Regency is one of the areas that has the potential to develop Robusta coffee with a productivity of 875 kg/ha. The involvement of marketing agencies that carry out marketing functions results in differences the price of Robusta coffee. This study aims to find out how the condition of the marketing channel, the implementation of marketing functions, and the efficiency of the marketing channel for Robusta coffee in Bogor Regency. This study took a sample of 50 farmer respondents using purposive sampling method and 12 marketing agencies using snowball sampling method. The analytical method used is descriptive qualitative for channels and functions of marketing agencies. Quantitative analysis methods for calculating marketing margins, farmer’s share, profit and cost ratios, and marketing efficiency are then described qualitatively. The results showed that there were two types of marketing channels for Robusta coffee in Bogor Regency, namely general and special marketing channels. What distinguishes it is the treatment given to the green beans produced. General marketing channels consisting of marketing channels 1, 2, and 3 originate from random quotations, while special marketing channels consisting of marketing channels 4 and 5 originate from red quotations. Relative efficiency in general marketing channels is in marketing channel 3 with the smallest margin value and marketing efficiency level, while in special marketing channels is in marketing channel 4 and also the dominant marketing channel. Adoption of technology, infrastructure improvements, and optimizing the existence of farmer groups are inputs for maximizing the quality and quantity of green beans.